2004
DOI: 10.1111/j.1440-183.2004.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and AFLP variation of Porphyra yezoensis Ueda form, narawaensis Miura (Bangiales, Rhodophyta)

Abstract: Detailed morphological observations were made on two strains of cultivated Porphyra : HG-1 (pure line isolated from Dai-1) and Noriken-4 (parental strain of a pure line HG-4) . The two strains were identified as P. yezoensis f. narawaensis based on their macroscopic and microscopic features, such as long linear or oblanceolate blades up to 50 cm in maximum length, division formulae of spermatangia and zygotosporangia, shape of trichogynes and carpogonia, and the second transverse divisional plane formed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 14 publications
0
49
0
3
Order By: Relevance
“…The self‐fertilized conchocelis released homozygous conchospores that could grow into blades with a high degree of genetic similarity, whereas cross‐fertilized conchocelis released heterozygous conchospores that could grow into blades with a low degree of genetic similarity (Niwa et al. , Li et al. , Shan and Pang ).…”
Section: Discussionmentioning
confidence: 99%
“…The self‐fertilized conchocelis released homozygous conchospores that could grow into blades with a high degree of genetic similarity, whereas cross‐fertilized conchocelis released heterozygous conchospores that could grow into blades with a low degree of genetic similarity (Niwa et al. , Li et al. , Shan and Pang ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we identified wild and cultivated strains of P. yezoensis and P. tenera by combining morphological observations and molecular analyses (Niwa and Aruga 2003, Niwa et al. 2004, 2005a,b, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Until the mid 1950s, 11 species were cultivated in Japan, and Porphyra tenera and Porphyra yezoensis were the main species of marine crop (Miura 1988). However, with the progress of Porphyra breeding, P. yezoensis f. narawaensis A. Miura, a vigorously growing cultivar with more elongate blades (Miura 1984, Niwa et al. 2004, 2008a), has more recently become the most commonly used strain in Japanese nori farms (Niwa and Aruga 2003, 2006, Niwa et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1999). It is therefore easy to isolate pure lines (complete homozygous conchocelis strains) with target genotypes via the self‐fertilization of blades developed from archeospores released from cell clusters in haploid blades (Niwa et al. 2004).…”
Section: Porphyra Strains Used In the Experimentmentioning
confidence: 99%